Effect of Noni Extract (Morinda citrifolia L.) on Spermatozoa Quality of Mice (Mus musculus L.) - Mita Ariani; Ardelia Febriana; Feby Djumaita Sari; Khairunisa Khairunisa; Yusni Atifah; Helsa Rahmatika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2023)
This study aims to see the effect of giving noni extract (Morinda citrifolia L.) on the quality of spermatozoa of mice (Mus musculus L.). This study was conducted using an experimental method, with a completely randomized design (RAL), 3 treatments with 5 replicates with 15 male mice divided into three treatment groups, namely the control group (P0), the treatment group with a concentration of 0.3 g/BW (P1), and the treatment group with a concentration of 0.6 g/BW (P2) which then the data were analyzed using ANOVA. This research was conducted from March 2 to April 4, 2023. Observations of the effect of giving noni extract were made by making wet preparations of mice sperm and then observing under a microscope. Based on the research conducted, it was found that noni extract had a different effect from each concentration on motility and morphology in sperm. From the research, it can be concluded that the higher the concentration of noni extract given to mice will reduce the quality of sperm in mice However, at a concentration of 0.3 g/BB, it was found that noni had a positive effect on sperm morphology and motility in mice (Mus musculus L).